OzEAN Study to Collect Real-World Evidence of Persistent Use, Effectiveness, and Safety of Ozanimod Over 5 Years in Patients With Relapsing-Remitting Multiple Sclerosis in Germany - Ziemssen, Tjalf; Richter, Stephan; Mäurer, Mathias; Buttmann, Mathias; Kreusel, Boris; Poehler, Anne-Maria; Lampl, Maren; Linker, Ralf A. (Frontiers in Neurology, 2022)
Background: Ozanimod, a sphingosine 1-phosphate receptor 1 and 5 modulator, was approved as a disease-modifying therapy for active relapsing-remitting multiple sclerosis (RRMS) in 2020 and for active ulcerative colitis in 2021. Long-term, real-world studies in a nonselective population are needed. OzEAN is an ongoing study to assess the real-world effectiveness, safety, and persistent use of ozanimod and its impact on quality of life (QoL) in patients with RRMS over a 5-year period. Methods: This prospective, noninterventional, postmarketing authorization study will enroll 1300 patients (≥ 18 years of age) with active RRMS. The decision to initiate ozanimod must have been made before and independent from study participation. Enrollment began in March 2021. Recruitment is ongoing and will last for 36 months across 140 sites in Germany. Treatment-naive patients or those having prior experience with a disease-modifying therapy receive oral ozanimod 0.92 mg/day after an initial dose escalation, per the summary of product characteristics recommendations, for up to 60 months. Persistence with ozanimod treatment (primary endpoint) is assessed at month 60. Secondary endpoints include additional physician-reported outcomes (persistence at earlier time points, annualized relapse rate, Expanded Disability Status Scale score, cognition [Symbol Digit Modalities Test], and incidence of adverse events), and patient-reported outcomes (PROs) assessing patient satisfaction, adherence, and treatment modalities (Treatment Satisfaction Questionnaire for Medication, v1.4), disability (United Kingdom Neurological Disability Rating Scale), QoL (MSQOL-54 questionnaire), fatigue (Fatigue Scale for Motor and Cognitive Functions), and health economics (Work Productivity and Activity Impairment Questionnaire for Multiple Sclerosis [German v2.1]; Multiple Sclerosis Health Resource Survey, v3.0). A Multiple Sclerosis Documentation System with an internet-based e-health portal allows patients to view files and complete questionnaires. A safety follow-up will occur 3–8 months after the last ozanimod dose for patients who discontinue treatment early. Long-term results are anticipated after study completion in 2029. Yearly interim analyses are planned after enrollment has reached 25%. Conclusion: This is the first long-term, real-world study of ozanimod in patients with RRMS and, to our knowledge, the first noninterventional study utilizing a patient portal. These data will add to the safety/efficacy profile of ozanimod demonstrated in phase 3 trials.